Increasing incidence of colorectal cancer among the younger population in Sweden. Issue 4 (2nd June 2020) - Petersson, J.; Bock, D.; Martling, A.; Smedby, K. E.; Angenete, E.; Saraste, D.
Abstract : Background: The incidence of colorectal cancer in patients aged less than 50 years is increasing in Western countries. This population‐based study investigated the age‐ and sex‐specific incidence of colorectal cancer over time in Sweden, and characterized trends in tumour localization and stage at diagnosis. Methods: Patients diagnosed with colorectal cancer between 1970 and 2016 were identified from the Swedish Cancer Registry, and categorized by sex, age and tumour location. The incidence and average annual percentage change (AAPC) were estimated and compared between age groups. Results: There was an overall increase in the incidence of colorectal cancer between 1970 and 2006, but a decrease in 2006–2016 (AAPC −0·55 (95 per cent c.i. −1·02 to −0·07) per cent). The largest increase in colonic cancer was in 1995–2005 in women aged less than 50 years (AAPC 2·30 (0·09 to 4·56) per cent versus 0·04 (−1·35 to 1·44) and − 0·67 (−1·62 to 0·28) per cent in women aged 50–74 and 75 years or more respectively). Since 1990, rectal cancer increased in patients of both sexes aged below 50 years, with higher AAPC values in women (2006–2016: 2·01 (−1·46 to 5·61) per cent versus 0·20 (−2·25 to 2·71) per cent in men). Younger patients were more likely than those aged 50–74 and 75 years or more to present with stage III–IV colonic (66·2, 57·6 and 49·6 per cent respectively) and rectal (61·2, 54·3 and 51·3 per cent) cancer. From the mid 1990s, rates of proximal and distal colorectal cancer, and rectal cancer were increased in patients aged less than 50 years. Conclusion: The overall incidence of colorectal cancer in Sweden decreased in the past decade. However, in patients under 50 years of age the incidence of colorectal cancer – proximal, distal and rectal – continued to increase over time. Abstract : The overall incidence of colorectal cancer in Sweden increased between 1970 and 2006, with a decrease observed only in the last decade, 2006–2016. However, in patients younger than 50 years of age there was an ongoing increase, more marked in women. Early onset colorectal cancer in sweden Abstract : Antecedentes: La incidencia del cáncer colorrectal (CCR) en pacientes < 50 años está aumentando en los países occidentales. El objetivo de este estudio de base poblacional fue investigar las tendencias y la incidencia específica por edad y sexo del CCR a lo largo del tiempo en Suecia, así como caracterizar las tendencias en la localización tumoral y en el estadio del CCR en el momento del diagnóstico. Métodos: Los pacientes diagnosticados con CCR entre 1970 y 2016 fueron identificados a partir del Registro de Cáncer de Suecia. Se clasificaron por sexo, edad y localización del tumor. Se calcularon la incidencia media y el promedio del cambio porcentual anual ( average annual percentage change, AAPC), comparándose entre los grupos de edad. Resultados: Globalmente, la incidencia de CCR aumentó entre 1970‐2006, pero se observó una disminución de 0, 6% (i.c. del 95% ‐1, 02 a 0, 07) entre 2006‐2016. El AAPC del cáncer de colon aumentó con el tiempo tanto en mujeres como en varones. En particular, el mayor aumento se observó entre 1995‐2005 en mujeres de < 50 años, que presentaron un AAPC de cáncer de colon de 2, 3% (i.c. del 95% 0, 09 a 4, 56), mayor en comparación con los grupos de edad más avanzada (50‐74 años: 0, 04%; i.c. del 95% ‐1, 35 a 1, 44; grupo de edad 75+: ‐0, 67%; i.c. del 95% ‐1, 62 a 0, 28), aunque el análisis de datos proporcionó valores limitados de i.c del 95%. En los varones de < 50 años, el AAPC del cáncer de colon aumentó en un 1, 2% (i.c. del 95% ‐0, 80 a 3, 21) entre 2006‐2016, pero la diferencia no fue significativa en comparación con otros grupos de edad. Desde 1990, los cánceres rectales aumentaron en pacientes de < 50 años, en ambos sexos y en particular en mujeres más que en varones (2006‐2016: mujeres 2, 0%, i.c. del 95% −1, 46 a 5, 61 versus varones 0, 2%, i.c. del 95% ‐2, 25 a 2, 71). En comparación con los grupos de mayor edad, los pacientes de < 50 años tenían más probabilidades de presentar cáncer de colon en estadio III/IV (66%, 58% y 50% en los grupos de edad de < 50, 50‐74 y mayores de 75 años, respectivamente) y cáncer de recto (61%, 54% y 51% en los grupos de edad de < 50, 50‐74 y mayores de 75 años, respectivamente). Desde mediados de los 90 se observaron tasas cada vez mayores de CCR proximal, distal y de cáncer de recto en pacientes de < 50 años. Conclusión: La incidencia global de CCR en Suecia disminuyó en la última década. Sin embargo, en pacientes menores de 50 años, la incidencia del cáncer colorrectal, proximal, distal y rectal ha continuado aumentando a lo largo del tiempo.